Digital Tahfidz Integration for Forming Rabbani and Qurani Generations: Integrasi Digital Tahfidz untuk Membentuk Generasi Rabbani dan Qurani - Nurmalita, Distia Intan; Fahyuni, Eni Fariyatul (Journal of Islamic and Muhammadiyah Studies, 2025)
General Background: Early childhood education plays a critical role in shaping spiritual, moral, and cognitive development, particularly in Islamic contexts where tahfidz (Qur’an memorization) is foundational. Specific Background: KB-TK Al Muhajirin Islamic School seeks to integrate digital systems into tahfidz learning to address challenges of modern education, parental monitoring, and the need for innovative learning strategies. Knowledge Gap: Existing practices often rely on conventional methods, limiting access to real-time progress tracking and reducing engagement in digital-era learning. Aims: This study describes the school’s development plan to implement digital tahfidz-based learning, focusing on infrastructure, teacher training, program evaluation, and alignment with the school’s vision of forming Rabbani and Qurani generations. Results: The plan outlines structured steps for system implementation, review, real-time parental involvement, and continuous evaluation, facilitating more effective learning experiences. Novelty: The integration of a digital information system into early childhood tahfidz education is a pioneering approach in the local Muhammadiyah educational context. Implications: This model offers a scalable framework for other Islamic educational institutions aiming to modernize tahfidz learning while maintaining moral and spiritual objectives. Highlights: Digital tahfidz system enables real-time parental monitoring. Structured teacher training strengthens implementation and pedagogy. Continuous evaluation aligns learning with Rabbani and Qurani vision. Keywords: Digital Tahfidz, Early Childhood Education, Islamic School, Rabbani Generation, Qurani Generation